2020
DOI: 10.1071/fp19213
|View full text |Cite
|
Sign up to set email alerts
|

Effects of contrasting shade treatments on the carbon production and antioxidant activities of soybean plants

Abstract: In China, maize-soybean relay-intercropping system follow the two main planting-patterns: (i) traditional relay-intercropping; maize-soybean equal row planting, where soybean experience severe maize shading on both sides of plants, and (ii) modern relay-intercropping; narrow-wide row planting, in this new planting pattern only one side of soybean leaves suffer from maize shading. Therefore, in this study, changes in morphological traits, cytochrome content, photosynthetic characteristics, carbon status, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…Nevertheless, optimum planting geometry could improve resource use efficiencies in crops through proper crop phenology, producing more leaf area and ultimately more favorable yield components and yield in cereal crops in all climatic conditions 251,252 . Planting geometry affects solar radiation interception, canopy coverage, crop growth rate and biomass accumulation 215,[253][254][255][256][257][258] . Furthermore, with optimum planting geometry, total dry matter production and ultimately grain yield increase was mainly due to more photo-assimilates 252 .…”
Section: Adaptation Strategies In Response To Climate Changementioning
confidence: 99%
“…Nevertheless, optimum planting geometry could improve resource use efficiencies in crops through proper crop phenology, producing more leaf area and ultimately more favorable yield components and yield in cereal crops in all climatic conditions 251,252 . Planting geometry affects solar radiation interception, canopy coverage, crop growth rate and biomass accumulation 215,[253][254][255][256][257][258] . Furthermore, with optimum planting geometry, total dry matter production and ultimately grain yield increase was mainly due to more photo-assimilates 252 .…”
Section: Adaptation Strategies In Response To Climate Changementioning
confidence: 99%
“…In many past reports, scientists have reported that soybean suffers from heavy maize shading, especially during the co-growth phase 13 . Maize shading adversely affects the morphology (plant height and stem diameter), physiology (photosynthesis, chlorophyll structure, and concentration), and biochemistry (activities of antioxidants, sucrose, and starch accumulation) of intercropped soybean plants in MSR 28 30 . Therefore, intercropped soybean produces a lower yield in MSR as compared to sole soybean yield 13 , 31 .…”
Section: Introductionmentioning
confidence: 99%
“…The process of flower development into mature pods during the flowering and podding stage determines the number and quality of the soybean pod. Nutrition competition among sourced and sink organs caused flowers and pod abortion and abscission, decreasing soybean pod number and grain yield ( Raza et al, 2020 ). Nitrogen application at the R1 stage increased the soybean grain yield by promoting biomass accumulation during the soybean reproductive growth stage ( Zhou H. et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%